PRINSIP-PRINSIP PENDIDIKAN ISLAM SERTA RELEVANSI DALAM MENGHADAPI TANTANGAN GLOBALISASI - Yulia, Yulia; Sirozi, Muhammad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
Globalization has a significant impact on various fields such as economy, social, politics, culture and education. The beginning of globalization was marked by advances in information and communication technology. This has implications for various fields including education. Islamic education faces increasingly complex globalization challenges. In addition, globalization has a major impact on human thinking towards the outside world. Therefore, the principles of Islamic education must be discussed again, to face the challenges of globalization. The purpose of this study is to analyze the challenges of Islamic education in the era of globalization, and analyze the relevance of the principles of Islamic education in facing the challenges of globalization. The methodology used in this article is library research. Based on the results of my research, the challenges of Islamic education include three main problems, namely, the development of science and technology, the dichotomy of knowledge, and moral decline. While the principles that must be realized in facing global challenges such as, the principle of integration and proportional, the principle of human part of rububiyah, the principle of realizing the perfect human and the open principle. Based on this explanation, the author concludes that the basics in religious education are relevant in facing the challenges of globalization if realized properly and appropriately.